Roadmap and Reflections on Expanding Equity, Diversity, Inclusion, Indigeneity, and Accessibility in Pharmacology Curricula - Gurnit Kaur; Raveen Christian Joy Rajakumar; Zena Agabani; Michelle Arnot (Pharmacology Research & Perspectives)
ABSTRACT Nurturing learning systems that are respectful and welcoming to diverse individuals is a step towards improving the experience of all students in pharmacology and toxicology (Pharm‐Tox). This paper evaluates the Pharm‐Tox curriculum at the University of Toronto with a critical lens towards the incorporation of content that is Equitable, Diverse, Inclusive, acknowledges Indigeneity, and is Accessible (EDIIA). A curriculum mapping approach examined the undergraduate Pharm‐Tox curriculum to identify EDIIA gaps and areas for improvement. Key stakeholders that contributed to the curriculum mapping process were undergraduate students, teaching faculty, and an external research associate who identified EDIIA themes used to evaluate existing course materials. The curriculum map identified areas to improve EDIIA integration in individual courses and resulted in the design of course‐specific recommendations. Centrally housed department resources were also developed to mitigate barriers to faculty implementation of the EDIIA recommendations. These resources included an internal EDIIA handbook on appropriate language in the classroom, a guide to creating accessible and inclusive PowerPoint slides, and a pre‐course survey to identify the student population and their needs. Resources were well received by faculty, and to assess the impact of EDIIA recommendations on student learning, ongoing review of curricular changes will be conducted through student surveys. The recommendations from this curriculum mapping process encourage faculty to explore opportunities for EDIIA integration in the undergraduate Pharm‐Tox curriculum with the goal of strengthening the existing curriculum and improving the student learning experience.